Association between Mobile Phone Use and Physical Wellbeing - Amin, Md Nurul; Islam, Md Sultan Ul; Haque, Md Jawadul (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Mobile phones transmit information using radio waves through a network of fixed antennas. Radiofrequency waves are electromagnetic fields, and unlike ionizing radiation such as X-rays or gamma rays, can neither break chemical bonds nor cause ionization in the human body. However, a large number of studies performed over the last two decades claimed that exposure to radiofrequency electromagnetic fields (RF-EMF) from mobile phone have been linked with symptoms ill-health. But the studies were studded with shortcomings and their findings were inconsistent. The present study was therefore intended to see the status of physical health of cell-phone users and the potential effect of talk-time on haemodynaic stability, as an indirect evidence of impact of RF-EMF on haemodynamic variables. Methods: A cross-sectional analytical design was considered suitable for assessing physical symptoms associated with mobile phone use, while for assessing changes in haeodynamic state before and after a certain duration of phone call were studied with the help of within sample pre-test post-test design. The study was conducted in the Institute of Environmental Science (IES), Rajshahi University (RU), Rajshahi between July 2017 to June 2022. Data for the study were collected from medical students of Rajshahi Medical College (n = 118) and students from RU (n = 195). Having obtained written approval from the IES, Rajshahi University, Rajshahi and verbal approval from the Supervisor and the Co-supervisor, data were collected from the respondents with their consent, over a period of three months from October to December 2021 using a semi-structured questionnaire containing the variables of interest. However, respondents suffering from any serious illnesses (like fever on the day of interview) or had a history of hypertension were excluded. We used questionnaires to obtain self-reported information on headache, tinnitus, hotness or earache during call, hearing deficit, vertigo, irritability, sleeplessness or digital eye syndrome like dry eye, red-eye, blurred vision, lacrimation, eye strain, neck pain etc. Whether radiofrequency radiation emitted from the mobile phone cause rise of local temperature and changes in haemodynamic variables like pulse, systolic and diastolic blood pressures of respondents data were taken before and immediately after a phone call and the differences between the two data-set were analyzed. Result: The study demonstrated that respondents were invariably used to using Smartphone with mean duration of use being 6.8 ± 2.7 years. Investigating about profile of mobile use revealed that the median number of calls made and received daily (on an average) was 5(range: 1-55), the median of average duration of per call was 4 (range: 1-60) minutes with median duration of longest call daily being 10 (range:1-180) minutes. Overall, the users spent on an average 4.3±2.3 hours’ time daily on mobile. A considerable proportion of mobile users experienced irritability (38.7%), sleeplessness (30.7%), weekly headache (30.3%), hotness in the ear during call (22.4%), earache (19.5%), occasional vertigo (13.4%) and tinnitus (12.1%). The symptoms of computer vision syndrome or digital eye syndrome reported were blurred vision (37.1%), eye-strain or irritation (32.3%), lacrimation (28.8%), dry-eye (15%), red-eye (18.2%) and neck pain (17.5%). The local temperature was observed to be significantly increased by 0.6 0F after a median duration of 20 (range: 4 – 32) minutes talk (p < 0.001) with consequent increase in heart rate by 3 beats/min (p = 0.009). However, neither local temperature nor pulse immediately after quitting the call was found to bear any significant correlations with talk-time. Conclusion: The study concluded that a reasonable number of mobile users experienced irritability, sleeplessness, weekly headache, hotness in the ear during call, earache, occasional vertigo and tinnitus. The symptoms of computer vision or digital eye syndrome like blurred vision, eye-strain or irritation, lacrimation, dry-eye, red-eye and neck pain are also not unusual. The local temperature and heart rate are significantly increased with prolonged talk-time. Ibrahim Card Med J 2021; 11 (2): 8-15